The Impact of Education on Muslim Women's Roles: A Case Study of Child Upbringing and Home Management in Chinade Town, Bauchi State - Garba Sa'adu Kawu (RaSAIL Media Group, Semarang, Indonesia, 2024)
This study investigates the role of educated Muslim women in child upbringing and home management in Chinade Town, Katagum Local Government Area, Bauchi State, Nigeria, specifically examining the influence of core Islamic values, cultural transfer, and the prevalence of educated women within households. Utilizing a survey design, data were collected from a randomly selected sample of over 70 households. Descriptive statistical analysis, including mean and standard deviation calculations, examined the relationships between the aforementioned factors and women's roles. Findings indicate a significant relationship between the adherence to core Islamic values, the influence of external cultural elements, and the educational attainment of Muslim women with their approaches to child-rearing and household management. While this study acknowledges the presence of other potential influencing factors not examined herein, it underscores the importance of these key variables in understanding the dynamics of women's roles within this specific cultural context. Further research is recommended to explore additional factors, such as awareness levels and community development initiatives related to positive child upbringing and home management practices. Based on the findings, this study suggests that Islamic scholars and organizations should prioritize and advocate for increased access to both Islamic and Western education for Muslim women, recognizing their pivotal role in shaping family life and societal values.